1996
DOI: 10.1017/s0016756800007846
|View full text |Cite
|
Sign up to set email alerts
|

Intrusion age of Pan-African augen gneisses in the southern Menderes Massif and the age of cooling after Alpine ductile extensional deformation

Abstract: Pb-Pb single zircon ages of 546.2 ± 1.2 Ma demonstrate that the augen gneisses in the southern Menderes Massif were generated from Pan-African intrusions. During the Alpine orogenic evolution of the Menderes Massif these granites were metamorphosed and transformed into augen gneiss in an extensional top-to-the-south shear zone, located between augen gneisses and overlying schists. Quartz fabrics suggest a pronounced static recrystallization that post-dates the ductile deformation in the shear zone. Ar-Ar musco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
173
0
3

Year Published

1999
1999
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 178 publications
(183 citation statements)
references
References 17 publications
7
173
0
3
Order By: Relevance
“…U/Pb and Pb/Pb zircon ages cluster at around~550 Ma and are interpreted as intrusion ages of the precursors of the orthogneisses Gessner et al, 2004;Hasözbek et al, 2011;Hetzel & Reischmann, 1996;Koralay et al, 2011Koralay et al, , 2012Koralay et al, , 2004Loos & Reıschmann, 1999). The orthogneisses are interpreted as syn-to post Pan-African intrusions, related to the latest Neoproterozoic final amalgamation of the Gondwana Candan, Oberhän-sli et al, 2011;Hetzel & Reischmann, 1996;Koralay, Candan et al, 2011;Koralay et al, 2012). The granite to orthogneiss transformation is ascribed to both Neoproterozoic, and to the later Eocene Alpine metamorphism.…”
Section: General Stratigraphy Of the Late Neoproterozoic Basement Of mentioning
confidence: 97%
See 2 more Smart Citations
“…U/Pb and Pb/Pb zircon ages cluster at around~550 Ma and are interpreted as intrusion ages of the precursors of the orthogneisses Gessner et al, 2004;Hasözbek et al, 2011;Hetzel & Reischmann, 1996;Koralay et al, 2011Koralay et al, , 2012Koralay et al, , 2004Loos & Reıschmann, 1999). The orthogneisses are interpreted as syn-to post Pan-African intrusions, related to the latest Neoproterozoic final amalgamation of the Gondwana Candan, Oberhän-sli et al, 2011;Hetzel & Reischmann, 1996;Koralay, Candan et al, 2011;Koralay et al, 2012). The granite to orthogneiss transformation is ascribed to both Neoproterozoic, and to the later Eocene Alpine metamorphism.…”
Section: General Stratigraphy Of the Late Neoproterozoic Basement Of mentioning
confidence: 97%
“…Based on the mineralogical compositions and textural properties, several different types of orthogneisses have been distinguished: biotite orthogneiss, leucocratic tourmaline orthogneiss and amphibole orthogneiss (Bozkurt, Winchester, Mittwede, & Ottley, 2006;Koralay, Candan, Chen et al, 2012). U/Pb and Pb/Pb zircon ages cluster at around~550 Ma and are interpreted as intrusion ages of the precursors of the orthogneisses Gessner et al, 2004;Hasözbek et al, 2011;Hetzel & Reischmann, 1996;Koralay et al, 2011Koralay et al, , 2012Koralay et al, , 2004Loos & Reıschmann, 1999). The orthogneisses are interpreted as syn-to post Pan-African intrusions, related to the latest Neoproterozoic final amalgamation of the Gondwana Candan, Oberhän-sli et al, 2011;Hetzel & Reischmann, 1996;Koralay, Candan et al, 2011;Koralay et al, 2012).…”
Section: General Stratigraphy Of the Late Neoproterozoic Basement Of mentioning
confidence: 99%
See 1 more Smart Citation
“…The core rocks are composed mostly of augen gneiss, metagranite (granitic gneiss), schist and metagabbro (Candan, 1995;Satır & Friedrichsen, 1986). The age of the granitic protolith of the augen gneiss is Late Precambrian and Early Cambrian (521-572 Ma) based on the U-Pb and Pb-Pb single zircon evaporation methods (Gessner et al, 2001;Hetzel & Reischmann, 1996;Loos & Reischmann, 1999). The second major rock assemblage comprising the Menderes Massif is known informally as the Cover.…”
Section: Basement Rocksmentioning
confidence: 99%
“…The nature of the discontinuity or contact between the so-called "Core" and "Cover" rocks is still under debate. There are three ideas about it: (1) it is a regional unconformity (the supra Pan-African unconformity) (Şengör, Satır, & Akkök, 1984), (2) it is a south-facing extensional shear zone including preserved igneous contact along which Oligo-Miocene granites were intruded into the cover rocks (Bozkurt, 2004;Bozkurt, Park, & Winchester, 1993;Bozkurt & Satır, 2000;Hetzel & Reischmann, 1996); these authors have also reported that the core rocks had been exhumed into their present-day positions in the footwall of this shear zone during a top-to-the SSW operating deformational event of Oligo-Miocene age, and (3) it is a south-facing thrust fault contact (Gessner et al, 2001;Ring, Gessner, Güngör, & Passchier, 1999). The Menderes Massif has attained its massif character under the high-T (500°)/ moderate-P (≤5 kbar) conditions or Barrovian-type of tectono-metamorphic event termed "main Menderes metamorphism (MMM)" (Whitney & Bozkurt, 2002).…”
Section: Basement Rocksmentioning
confidence: 99%